The European Commission's Light Bulb Decree: Another Costly Regulation? - Manuel Frondel; Steffen Lohmann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
Since September 2009, Regulation 244/2009 of the European Commission enforces the gradual phase-out of incandescent light bulbs. As of September 2012, only energy-efficient lighting sources will be allowed for sale. Among these are halogen light bulbs, light-emitting diodes (LED), or compact fluorescent light bulbs - often referred to as energy-saving light bulbs. The Commission's justification for the phase-out of conventional light bulbs maintains that a reduction in the electricity consumed will not only lead to lower energy cost for private households and industrial consumers, but at the same time lead to a decrease in greenhouse gas emissions. This article discusses possible reasons for the slow market diffusion of energy-saving light bulbs and shows that the investment in energy-efficient light bulbs does not necessarily lead to significant cost reductions. Drawing on some illustrative examples, we demonstrate that the use of cheaper incandescent bulbs instead of energy-saving light bulbs can be economically rational in cases of rather low usage times, in which the higher initial purchasing price might only pay off after very long time spans. Furthermore, due to the coexistence with the European Emissions Trading Scheme (ETS), this regulation attains no additional emission reductions beyond those achieved by the ETS alone. We thus conclude that the general ban of incandescent light bulbs is inappropriate and should be abolished by the Commission. – – In der 2009 in Kraft getretenen EG-Verordnung 244/2009 ist das schrittweise Handelsverbot von Glühbirnen in der Europäischen Union festgelegt. Ab dem 1. September 2012 dürfen ausschließlich energieeffiziente Leuchtkörper, wie etwa Halogenleuchten, Leuchtdioden (LED) oder Kompaktleuchtstofflampen, welche gemeinhin als 'Energiesparlampen' bezeichnet werden, in den Verkauf gelangen. Die häufig als Glühbirnenverbot betitelte Verordnung wird von der EU-Kommission vor allem mit Strom- und Kosteneinsparungen bei den Verbrauchern und der Verringerung des Ausstoßes an Treibhausgasen gerechtfertigt. Dieser Beitrag diskutiert mögliche Ursachen für die bislang mangelnde Marktdurchdringung der Energiesparlampe und zeigt, dass durch die Investition in eine Energiesparlampe nicht in jedem Falle signifikante Kosteneinsparungen erzielt werden können. So können die gegenüber der herkömmlichen Glühbirne höheren Investitionskosten bei sehr geringen Nutzungszeiten nur nach sehr langen Zeiträumen ausgeglichen werden. Anhand von Beispielen illustrieren wir, dass der Einsatz von Energiesparlampen in vielen Fällen ökonomisch wenig rational ist. Allein aus diesem Grund sollte das generelle Glühbirnenverbot der EU-Kommission wieder zurückgenommen werden. Den Verbrauchern könnte dadurch einiger Schaden erspart bleiben, schließlich ist die am häufigsten verwendete 60-Watt-Glühbirne erst ab 1. September 2011 vom EU-Verbot betroffen.
Keywords: D12; Q41; 330; energy efficiency; rebound effect